La notion de «mot» en marge de l’analyse linguistique - Vitez, Primož (Vestnik za tuje jezike, 2024)
The article aims to examine the analytical potential of the metalinguistic concept of the “word”. It is at the same time an important pre-theoretical concept since any language user is free to exploit it in any of its numerous variants in polysemic dimensions. Considering the criteria of grammatical description, this concept first opens the question of delimitation between the morphological and syntactic analysis of linguistic structures. In writing, the problem of definition seems less complex because it is relatively easy to discern a continued series of graphic signs (i.e. letters) between two blanks. Even if the morphosyntactical criteria seem less obscure in writing, it is in the nature of orthography to sometimes hesitate to determine the extension of the word as a graphical unit. In the long term, linguistic practice causes changes that later systemic prescriptions choose or refuse to adopt. The semantic supposition that the word – as an autonomous unit of meaning – refers to a particular segment of extralinguistic reality is hardly more precise: the case of compound French nouns (porte-manteau, quatre-vingts, grand-mere etc.) problematizes these semantic units, making it hard to decide whether their structure consists of one word or two.Reflecting on the word very concretely raises the question of the relationship between lan-guage and its use. It seem that, to define the word, it is imperative to take into account the oral manifestations of linguistic use and therefore privilege the analysis of accentuation. Even if the division into accent segments does not affect the lexemic unit, which is most often the case in languages with non-fixed accents, the word (or at least the phonetic word) is a unit of meaning that the accent allows us to recognize. The word is therefore also definable as an accentual unit.
Keywords: accent; beseda; enota jezikoslovne analize; govor; linguistic analysis unit; morphosyntax; naglaševanje; oblikoskladnja; orality; word